Perubahan Budaya Bermukim Masyarakat di Kawasan Tepian Sungai Musi - Husnul Masyitoh; Agung Budi Sardjono (Universitas Sebelas Maret Surakarta, 2026)
Changes in the Settlement Culture of Communities Along the Musi RiverThe settlements along the Musi River are an important part of the cultural identity of the indigenous people of Palembang, as they reflect local customs and distinctive traditional house architecture. However, the culture of living along the riverbank has gradually shifted to inland areas. This study aims to analyze the forms of change in the settlement culture of the Musi Riverbank community from the past to the present and to identify the factors causing these changes, particularly in the areas of Ki Gede Ing Suro, 32 Ilir, and 35 Ilir. This research employed an exploratory qualitative method through field observations, interviews, and an examination of the socio-cultural conditions of the community. The results indicate a shift in settlement patterns from riverbank dwellings to inland settlements. These changes are influenced by environmental, social, and economic factors, infrastructure development, as well as changes in the community’s living needs.